The impact on productivity costs of reducing unemployment in patients with advanced breast cancer: A model estimation based on a Portuguese nationwide observational study - Leonor Vasconcelos de Matos; Margarida Borges; Ana Teresa Oliveira; Carolina Bulhosa; Luís Silva Miguel; Tiago Fidalgo de Freitas; Renato Cunha; Ana Duarte Mendes; Ana Júlia Arede; Cristiana Marques; Diogo Alpuim Costa; Jorge Alves Correia; et al. (Breast)
This study aimed to characterize the employment status and work-related conditions of patients with advanced breast cancer (ABC) in Portugal and quantify the productivity costs of premature abandonment of the work market while evaluating strategies to promote employment. The analysis was based on a cumulative incidence model for estimation of ABC prevalence and on a cross-sectional study characterizing the employment status of patients with ABC. This study was conducted in Portuguese hospitals, between Nov2021-Dec2022 and included patients diagnosed with ABC for at least 6 months, aged 66 or less and consenting for a self-answered questionnaire regarding work status. A total of 2151 working-aged women were estimated to have ABC in 2019 in Portugal, with productivity costs amounting to 28,676,754€ over 2019–2021. 112 patients from 9 hospitals were included in the study, average age was 52yr, 48 % had a postsecondary educational degree level and 87 % reported having a paid job at the time of diagnosis, mostly full-time. At the time of the study, only 38 % of the patients maintained the job status. The remaining were unemployed (51 %), on medical leave (25 %) or retired (24 %). Stop working was a personal choice for only 5 %. A subsidized part-time employment regimen, despite increased government costs, would allow a reduction in productivity costs, leading to a positive balance of 2,431,329€ over the same period. This study suggests that the majority of patients with ABC abandon the labor market before the age of retirement. Flexible work arrangements would benefit the patient, the government and the society. ‘